Investigation of diamond-like carbon/silicon heterojunctions deposited by pulsed Nd:YAG laser - YAP, S; TOU, T (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Diamond-like carbon (DLC) films were deposited on p-type silicon (Si-100) substrates by using a pulsed Nd:YAG laser for the ablation of a pyrolytic graphite target at a background pressure of 10(-6) Torr. For a fixed distance of 3 cm between the target and substrate, samples of DLC/Si heterojunction were prepared for two different laser wavelengths of 355 nm and 1064 nm. All DLC films showed typical D and G bands in their Raman spectra. DLC films were also deposited on glass substrates for resistivity measurement by four-point probe. The electrical properties for DLC/Si heterojunctions were analyzed cutrent-voltage measurement at room temperature in the dark and also under illumination. The dependencies of the electrical characteristics on the depositing parameters were discussed. (C) 2008 Elsevier Ltd. All rights reserved.